Middle East Respiratory Syndrome-coronavirus infection: An overview - Jaffar A. Al-Tawfiq (Journal of Infection and Public Health, 2013)
Summary: Middle East Respiratory Syndrome-coronavirus (MERS-CoV) was reported from a number of countries in the Middle East and Europe with a reported high mortality rate. MERS-CoV was initially isolated from a patient from Bisha, Saudi Arabia. A recent outbreak of MERS-CoV infection was described in a healthcare facility. Although, the recent publications on this topic had shed light on the epidemiology of the disease, many questions remain to be answered. Keywords: Novel coronavirus, MERS-CoV, Middle East Respiratory Syndrome